New propolis type from north‐east Brazil: chemical composition, antioxidant activity and botanical origin. (8th February 2017) - Ferreira, Joselena M; Fernandes‐Silva, Caroline C; Salatino, Antonio; Negri, Giuseppina; Message, Dejair
Abstract: BACKGROUND: Propolis is a bee product with wide diversity of biological activity. It has a complex composition, which is dependent on its botanical source. The present study aimed to determine the chemical profile, antioxidant activity and botanical origin of two samples of a propolis type from two locations of the state of Rio Grande do Norte (RN, north‐east Brazil). RESULTS: The standard chemical characteristics of the RN propolis are similar or superior to the internationally marketed Brazilian green propolis. RN propolis from two locations have high antioxidant activity, corresponding to 10% (municipality of Afonso Bezerra) and 13% (municipality of Alto do Rodrigues) of quercetin activity by the 2, 2‐diphenyl‐1‐picrylhydrazyl method and to 15% (both locations) by the β ‐carotene discoloration method. High‐performance liquid chromatography with diode array detection (HPLC‐DAD)‐electrospray ionization‐tandem mass spectrometry analyses revealed that most constituents of the RN propolis are flavonoids, mainly flavonols and chalcones. HPLC‐DAD analysis of ethanol extracts revealed a great similarity between the chemical profile of RN propolis and shoot apices of 'jurema‐preta' ( Mimosa tenuiflora, Leguminosae, Mimosoideae). CONCLUSION: 'Jurema‐preta' shoot apices are likely resin sources of RN propolis. The chemical characteristics and antioxidant property of RN propolis provide promising prospects for the introduction of this type of propolis into the apicultural market. © 2017 Society of Chemical Industry